Cats & dogs [videorecording (DVD)] - Goldblum, Jeff, 1952-; Perkins, Elizabeth, 1960-; Pollock, Alexander (Warner Home Video, 2007)
Know to be man's best friends, cats and dogs have engaged in a fierce and merciless battle. Now, Mr. Tinkles, a ruthless cat, is plotting intensively to achieve nothing less than world domination. His main target is Professor Brody. The professor is working on a medication that will rid people of their dog hair allergies. Mr. Tinkles strives to get to the substance and have it analyzed. He then means to have it altered so that all humans of the world become allergic to any kind of dog. Cats would rule and dogs would then be exterminated. Lou is the Brody family's new puppy. He has never heard of dog agents and the major protective mission they fulfill towards the unsuspecting Brody family. Lou, along with Butch and a few other dog agents from the neighborhood desperately tries to hinder Mr. Tinkles in his sinister plans to take over the world.